PEMBUATAN MEDIA PROMOSI E-CATALOG DENGAN MENGGUNAKAN APLIKASI CANVA DI INSTAGRAM UNTUK MENARIK MINAT BELI PADA HALTER COFFEE MALANG - Muhammad Amrullah Sukma Wala; Joni Dwi Pribadi (CV. ALIM'SPUBLISHING, 2025)
This study aims to create an e-catalog using the Canva application as a promotional medium on Instagram to attract buying interest at Halter Coffee Malang. This research used action research methods. Methods of data collection used the methods of observation, interviews and questionnaires. The questionnaires were distributed to 2 part of the company, 2 design experts, and 30 potential customers. The results of the questionnaire were then analyzed by simple tabulation analysis and the average score was then analyzed by correlation coefficient to determine the relationship between the two variables. Based on the results of the research, it can be concluded that the e-catalog at Halter Coffee Malang deserves to be published. Therefore, it is hoped that Halter Coffee Malang can use this e-catalog as a promotional medium